Training and further education of teachers in correctional institutions. American and European literature - Miklósi, Márta (Form@re - Open Journal per la formazione in rete, 2025)
Teachers working in juvenile correctional facilities face a complex set of challenges, as not only the characteristics of the students but also the challenges of the special environment make their work difficult. The most important consideration in the operation of correctional institutions is safety, so all activities are subordinated to this, and teachers often must perform their work in these difficult circumstances without sufficient preparation. It varies from country to country whether teachers working in juvenile correctional institutions receive such training, and if so, to what extent and depth, although this is necessary, because university teacher training typically prepares future teachers for knowledge transfer. It would be important to specialise in the training of teachers who wish to work in correctional institutions within the teacher training system by incorporating several subjects that are particularly important for them. Formazione iniziale e continua degli insegnanti negli istituti penitenziari. Una rassegna della letteratura americana ed europea. Gli insegnanti che lavorano negli istituti di correzione minorili devono affrontare una serie complessa di sfide, poiché non solo le caratteristiche degli studenti, ma anche le difficoltà legate all’ambiente speciale rendono il loro lavoro difficile. La considerazione più importante nel funzionamento degli istituti di correzione è la sicurezza; quindi, tutte le attività sono subordinate a questo aspetto e gli insegnanti spesso devono svolgere il loro lavoro in queste difficili circostanze senza una preparazione adeguata. A seconda del Paese, gli insegnanti che lavorano negli istituti penitenziari minorili ricevono o meno una formazione specifica e, se sì, in che misura e con quale approfondimento, sebbene ciò sia sicuramente necessario, poiché la formazione universitaria degli insegnanti prepara tipicamente i futuri docenti al trasferimento delle conoscenze. Sarebbe importante specializzare la formazione degli insegnanti che desiderano lavorare negli istituti penitenziari all’interno del sistema di formazione degli insegnanti, incorporando diverse materie particolarmente importanti per loro.